2023
DOI: 10.1038/s41419-023-05565-x
|View full text |Cite
|
Sign up to set email alerts
|

WTAP-mediated m6A modification modulates bone marrow mesenchymal stem cells differentiation potential and osteoporosis

Abstract: An imbalance in the differentiation potential of bone marrow mesenchymal stem cells (BMSCs) is an important pathogenic mechanism underlying osteoporosis (OP). N6-methyladenosine (m6A) is the most common post-transcriptional modification in eukaryotic cells. The role of the Wilms’ tumor 1-associated protein (WTAP), a member of the m6A functional protein family, in regulating BMSCs differentiation remains unknown. We used patient-derived and mouse model-derived samples, qRT-PCR, western blot assays, ALP activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In addition to abovementioned miR-320, further studies uncovered that METTL3 can methylate pri-miR-21 and facilitate the maturation of miR-21 [ 55 ], which potentiates the osteogenesis of BMSCs by activating the Smad1/5/8-RUNX2 pathway [ 56 ] and lowering the amount of hypoxia-inducible factor-1α (HIF-1α) [ 57 ]. WTAP, another critical component of m 6 A writers, also acts as a promoter of osteogenesis by encouraging mature miR-29b-3p [ 58 ] and miR-181a/c [ 59 ]. Similar phenomenon was observed between METTL14 and miR-873 [ 60 ].…”
Section: A Modification and Osteogenesis Of Bmscsmentioning
confidence: 99%
“…In addition to abovementioned miR-320, further studies uncovered that METTL3 can methylate pri-miR-21 and facilitate the maturation of miR-21 [ 55 ], which potentiates the osteogenesis of BMSCs by activating the Smad1/5/8-RUNX2 pathway [ 56 ] and lowering the amount of hypoxia-inducible factor-1α (HIF-1α) [ 57 ]. WTAP, another critical component of m 6 A writers, also acts as a promoter of osteogenesis by encouraging mature miR-29b-3p [ 58 ] and miR-181a/c [ 59 ]. Similar phenomenon was observed between METTL14 and miR-873 [ 60 ].…”
Section: A Modification and Osteogenesis Of Bmscsmentioning
confidence: 99%
“…And whether BMSCs differentiate into osteogenic cells or adipocytes is linked to the pathogenesis of OP. Recent studies have revealed several mechanisms of m6A modifications to promoted osteogenic differentiation and inhibited adipogenic differentiation of BMSCs [ 137 , 141 , 147 ]. Growing evidences have shown the relationship between m6A modification and BMSC differentiation.…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…m6A modification is reversibly modulated through the installation of methyl transferases (writers), the removal of a methyl group by demethylases (erasers), and the recognition of m6A binding proteins (readers) [ 22 , 23 ]. m6A writers and associated proteins (m6A writer complex) include Vir-like m6A methyl transferase-associated protein (VIRMA) [ 24 ], methyl transferase-like protein 3 (METTL3) [ 25 ], METTL4 [ 26 ], MTTL5 [ 27 ], METTL14 [ 28 ], METTL 16 [ 29 ], Wilms’ tumor 1 associated protein (WTAP) [ 30 , 31 ], RNA-binding motif protein 15/15B (RBM15/15B) [ 32 ], casitas B-lineage lymphoma-transforming sequence-like protein 1 (CBLL1) [ 33 ], zinc finger CCCH-type containing 13 (ZC3H13), and zinc finger CCHC-type containing 4 (ZCCHC4) [ 5 , 34 , 35 , 36 , 37 , 38 ]. RBM15/15B, VIRMA, CBLL1, ZCCHC4, and ZC3H13 act as associated proteins of m6A writers.…”
Section: Regulators Of Rna Methylationmentioning
confidence: 99%